Sexagem molecular em Xenarthras, avaliação espaço-temporal de atropelamentos em tamanduás e diversidade genética em Myrmecophaga tridactyla: implicações para conservação - Barragán-Ruiz, Carmen Elena (2020)
It is expected that species that live in highly fragmented environments and have biological characteristics such as specialized diet, long generation time and low fecundity, tend to suffer more from anthropic impacts, modifying their biology, ecology and genetics. Using a total of 581 biological samples from carcasses as well as tissue samples from living (captured) individuals of Myrmecophaga tridactyla and Tamandua tetradactyla, we performed: (I) the identification of the sex of the individuals collected, using two nuclear sequences (SRY and Zinc finger); (II) the temporal and spatial evaluation of the groupings of the run over points for the two species, using road ecology approaches (III) the evaluation of the genetic diversity and demographic changes of the threatened species, M. tridactyla. Thus, we found that there was (I) an 87 % amplification success rate in the method used, achieving the identification of 151 males run over for 82 females run over in the species M. tridactyla (2:1), and 128 males run over for 51 females run over in the species T. tetradactyla (3:1). Additionally, (II) we did not find temporal variables (climatic) that would explain the number of run over of the species, but we did find a seasonal pattern responded by the females of the species. A total of ten hotspots of running over were found for both species (five for each), however, the evaluation of spatial variables that could explain the hotspots was not explanatory. Models constructed with spatial variables across the landscape (e.g. percentage of vegetation) explained for M. tridactyla 27 % of the variation found, while for T. tetradactyla 39 %. Finally, (III) we found no signs of reduced gene flow and moderate genetic diversity (Ho = 0.53) for M. tridactyla. Additionally, we found a coefficient of inbreeding of 0.13 (p ≤ 0.05) along with signs of reduction in effective population size of the species. In conclusion, we found evidence of the impact of roads on anteater species in the central western region of Brazil and therefore we recommend that our data be used for the evaluation of mitigation measures in the area.